[Association between the frequency of bowel movements and the risk of colorectal cancer in Chinese adults]. - Yang, S; Shen, Z; Yu, C; Guo, Y; Bian, Z; Tan, Y; Pei, P; Wei, Y; Chen, F; Chen, J; Chen, Z; Lyu, J; et al. (Chinese Journal of Epidemiology, 2019)
Objective: To examine the association between the frequencies of bowel movement (BMF) and the risk of colorectal cancer (CRC). Methods: In this study, 510 134 participants from the China Kadoorie Biobank (CKB) were included, after excluding those who reported as having been diagnosed with cancer at the baseline survey. The baseline survey was conducted from June 2004 to July 2008. The present study included data from baseline and follow-up until December 31, 2016. We used the Cox proportional hazards regression models to estimate the HR and the 95%CI of incident CRC with BMF. Results: During an average follow-up period of 9.9 years, 3 056 participants were documented as having developed colorectal cancer. In the site-specific analysis, 1 548 colon cancer and 1 475 rectal cancer were included. Compared with participants who had bowel movements on the daily base, the multivariable-adjusted HR (95%CI) for those who had more than once of BMF were 1.24 (1.12-1.39) for CRC, 1.12 (0.95-1.31) for colon cancer, and 1.37 (1.18-1.59) for rectal cancer. We further examined the association between BMF and CRC, according to the stages of follow-up, the corresponding HR (95%CI) for CRC, colon and rectal cancer were 1.59 (1.36-1.86), 1.43 (1.14- 1.80), and 1.76 (1.41-2.19) for the first five years, while such associations became statistically insignificant in the subsequent follow-up (P for all interactions were <0.05), as time went on. As for CRC, colon or rectal cancers among participants who had lower bowel movements, the risks were not significantly different from those who had bowel movements everyday. Conclusions: Participants who had BMF more than once a day, appeared an increased risk of CRC in the subsequent five years. Since abnormal increase of bowel movements is easily recognizable, programs should be set up on health self- management and early screening for CRC.